Utilization of Locally Available Feeds to Develop Sustainable Blue Swimming Crab (Portunus pelagicus) Farming in Central Java - Ariyati, Restiana Wisnu; Trienes, Yoni; Rejeki, Sri; Hutabarat, Johannes; Haeruddin, Haeruddin; Sarjito, Sarjito; Saputra, Suradi Wijaya; Widowati, Lestari Lakhsmi; Schrama, Johan; Bosma, Roel H. (Marine Science Department Diponegoro University, 2024)
The popularity of the blue swimming crab (Portunus pelagicus) has led to significant overfishing. Aquaculture offers a potential solution to reduce fishing pressure, given that P. pelagicus is relatively easy to hatch, has high fecundity, a short larval duration, and rapid growth. However, knowledge about feed preferences and feed-use efficiency in P. pelagicus is limited. This study compared the effectiveness of three locally available feeds. A total of 160 juvenile P. pelagicus were divided into five repetitions across four diet groups: PPV (shrimp pellets + Perna viridis flesh, crude protein = 45 %), PAI (shrimp pellets + Acetes indicus, crude protein = 45 %), P100 (shrimp pellets, crude protein = 30%), and P150 (shrimp pellets at 150% of the dry matter requirement, crude protein = 45%, iso-protein to both PPV & PAI). The experiment consisted of three phases: a one-week pre-trial to determine feeding rates, followed by a six-week culture period (Period-1) and an eight-week culture period (Period-2). Body weight and survival were measured biweekly, feed amounts were adjusted accordingly, and costs were recorded. Survival rates and feed conversion ratios were similar across all diets. Crab growth was lower in Period-2 than in Period-1 across treatments. The specific growth rates for PPV, PAI, and P150 were comparable, while P100 resulted in lower growth. The cost of PPV was higher than that of PAI, P100, and P150, with the economic feed conversion ratio for P100 and P150 outperforming PPV and PAI. Shrimp pellets proved to be an efficient feed for the grow-out phase of blue swimming crabs, though pellet size should match the crab’s size.